TRADISI PULANG BAINDUOK DI DESA PENYASAWAN KECAMATAN KAMPAR KABUPATEN KAMPAR - Winardi, Hary; Tantoro, Swiss (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research was conducted in the Penyasawan village; Kampar District with the research questions was (1) how is the process of pulang bainduok tradition implemented in Kampar District? (2) What is the meaning of pulang bainduok tradition in the Penyasawan Village, Kampar District? The purpose of this study was to find out the process of pulang bainduok tradition in the village of Penyasawan Kampar District and to find out the meaning of pulang bainduok tradition in the Penyasawan village, Kampar District. This research was descriptive research. There were 8 informants determined intentionally and selected by purposive sampling technique. The data was taken from primary data, namely direct data concerning the opinions of informants about the research variables obtained from the interview and secondary data, namely the data obtained to complete the primary data. The data collection technique were in the form of observations, interviews, and documentations. The findings of the research study showed that the tradition of Pulang Bainduok was very suitable for those people who prioritize family and empathy. The tradition of pulang baindouk to the village was only done for those who live in the Penyasawan village want to find tribes and relatives (induok). The meaning of this tradition was to provide protection for new comers who settled in the village of the Survivors. The benefit of having pulang bainduok tradition was to get a new family, to be able to gather with relatives so that the relationship between relatives and nephew is getting closer. One of the intentions of pulang bainduok is to give a status or tribe to new comers who want to settle down and marry a native woman of the Penyasawan village by looking for induok (family).Keywords: New Comers, Tradition, Pulang Bainduok.